2014
DOI: 10.1007/s12035-014-8722-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols as Therapeutic Molecules in Alzheimer’s Disease Through Modulating Amyloid Pathways

Abstract: Alzheimer's disease (AD) is a complex and multifactorial neurodegenerative condition. The complex pathology of this disease includes oxidative stress, metal deposition, formation of aggregates of amyloid and tau, enhanced immune responses, and disturbances in cholinesterase. Drugs targeted toward reduction of amyloidal load have been discovered, but there is no effective pharmacological treatment for combating the disease so far. Natural products have become an important avenue for drug discovery research. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 137 publications
0
99
0
Order By: Relevance
“…Results from the study show that compounds containing at least two aromatic structures (phenyl rings) and three hydroxyl groups linked with two to six atom linkers were effective anti-amyloid compounds (Porat et al 2006). Two other studies have also shown that the numbers of phenyl rings and hydroxyl groups, as well as their positions, on the molecules are important characteristics that determine the effectiveness of the aromatic compounds in their inhibition of A" aggregation (Lakey-Beitia et al 2014;Begum et al 2008).…”
Section: Aromatic Small Moleculesmentioning
confidence: 93%
See 2 more Smart Citations
“…Results from the study show that compounds containing at least two aromatic structures (phenyl rings) and three hydroxyl groups linked with two to six atom linkers were effective anti-amyloid compounds (Porat et al 2006). Two other studies have also shown that the numbers of phenyl rings and hydroxyl groups, as well as their positions, on the molecules are important characteristics that determine the effectiveness of the aromatic compounds in their inhibition of A" aggregation (Lakey-Beitia et al 2014;Begum et al 2008).…”
Section: Aromatic Small Moleculesmentioning
confidence: 93%
“…Flavonoids are plant secondary metabolites and are a subclass of the naturally-occurring polyphenols. Flavonoids have long been known for their multi-faceted pharmacology, including anti-inflammatory, anti-oxidant, anti-tumorigenic, anti-cancer, antimicrobial, and anti-vascular properties (Ringman et al 2005;Lakey-Beitia et al (2014); Kang et al 2005). The diverse range of biological properties appears to stem from the ability of this class of compounds to bind to a multitude of cellular targets, and thereby regulate multiple cellular pathways (Ringman et al 2005;Ramassamy 2006).…”
Section: Aromatic Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-flavonoids showed higher anti-aggregation activity than flavonoids. Polyphenols containing a higher number of aromatic rings, hydroxyl and keto groups and possess a high degree of planarity, have the largest inhibititory activity [18]. A structure-function relationship study suggested that the presence of at least two phenolic rings with two to six atomlong linkers, along with a minimum number of three hydroxyl groups on the aromatic rings, are essential for effi-cient inhibition exerted by polyphenols [5].…”
Section: Introductionmentioning
confidence: 99%
“…AD neuropathology is characterized by intraneuronal neurofibrillary tangles and extracellular senile plaques in the brain. Neurofibrillary tangles are composed of hyperphosphorylated tau proteins, while senile plaques originate from amyloid-β (Aβ) aggregation [1]. …”
Section: Introductionmentioning
confidence: 99%